Evaluating efficiency in Project management offices: a longitudinal evaluation using data envelopment analysis - Coelho, Marilia Botelho (2024)
A project is a temporary effort to create a unique product, service or result. Due to their temporary nature, they have a life cycle made up of six processes: initiation, planning, execution, monitoring, control and closure. Thus, they combine a set of desirable results and organizational resources throughout each process, using an approach structured in metrics and standards with the aim of meeting the demands and opportunities of organizations. Projects represent a way of keeping companies growing and competitive in a scenario of increasing change and technological demands. As a result, more and more organizations are investing in projects as a way of increasing their results and becoming competitive in the market. Project Management Offices are part of this context with a central responsibility for efficient management within organizations, being the central point of support for outlining metrics and standards that meet the business strategy. The PMO is a structure in the organization that is established in order to standardize how projects are managed and to ensure efficiencies by generating best practices from the delivery of a project portfolio. PMOs can be defined as a governance structure for organizational Project Management and many project-oriented companies are implementing a PMO. One of the indicators used in a company's PMO is the success of projects after they have been closed, thus assessing the effectiveness of the project. This strategy only looks at a few projects in the portfolio, with cost and maturity characteristics. Project maturity is reflected in the FEL methodology. The company uses this methodology to advance gates and thus evolve the maturity of the project scope over time and life cycle.